Mewujudkan Kedaulatan Ekonomi dan Pembangunan Nasional melalui Kesadaran Pajak Masyarakat - Wilma Silalahi; Anthony Sutedja (PT PUSTAKA CENDEKIA GROUP, 2025)
Tax is a form of revenue for a country and plays a very important role in maintaining the sustainability of the state. The definition of tax is a mandatory contribution paid by citizens to the government, which is coercive in nature and regulated by prevailing laws, without direct compensation, and is used to finance government expenditures for the benefit and welfare of the people within the country. In practice, however, various issues related to taxation still frequently occur, including its implementation, objectives, and system. One of the major problems faced today is the misuse of authority by certain government officials, where tax revenues that should be allocated to national development and public welfare are instead used for personal or familial enrichment.Another issue in the implementation of taxation in Indonesia is the lack of education and understanding among many citizens—especially those from lower-income groups—regarding the importance and benefits of paying taxes, as well as how the taxation system in Indonesia actually works. Therefore, it is essential to establish comprehensive education and socialization programs on taxation for all levels of society in Indonesia. The purpose of these efforts is to build economic sovereignty and national development through public awareness and participation, which should not only be the responsibility of government officials but also involve the active role of every citizen in supporting the implementation of taxation in Indonesia.